2017
DOI: 10.1152/ajprenal.00357.2016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex on hyperfiltration in patients with uncomplicated type 1 diabetes

Abstract: The aim of this analysis was to examine sex-based differences in renal segmental resistances in healthy controls (HCs) and patients with type 1 diabetes (T1D). We hypothesized that hyperfiltration-an early hemodynamic abnormality associated with diabetic nephropathy-would disproportionately affect women with T1D, thereby attenuating protection against the development of renal complications. Glomerular hemodynamic parameters were evaluated in HC ( = 30) and in normotensive, normoalbuminuric patients with T1D an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…We observed strong relationships between the later-stage renal outcomes and the nonmodifiable risk factors of male sex (for macroalbuminuria) and age (for reduced eGFR). The mechanisms for a putative protection in females from the incidence of macroalbuminuria are not known (31), although sex-specific influences on renal hemodynamic function have been reported (32). These differences may be through estrogenmediated effects on renin-angiotensinaldosterone system activation or possibly from sex-specific adiposity factors (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed strong relationships between the later-stage renal outcomes and the nonmodifiable risk factors of male sex (for macroalbuminuria) and age (for reduced eGFR). The mechanisms for a putative protection in females from the incidence of macroalbuminuria are not known (31), although sex-specific influences on renal hemodynamic function have been reported (32). These differences may be through estrogenmediated effects on renin-angiotensinaldosterone system activation or possibly from sex-specific adiposity factors (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for a putative protection in females from the incidence of macroalbuminuria are not known (31), although sex-specific influences on renal hemodynamic function have been reported (32). These differences may be through estrogenmediated effects on renin-angiotensinaldosterone system activation or possibly from sex-specific adiposity factors (32,33). The age-related decline in eGFR is well established in health and in disease and remains a consistent risk factor for reduced eGFR for both males and females in studies with sufficient sample size and study duration (34).…”
Section: Discussionmentioning
confidence: 99%
“…The lifetime risk of DN in T1DM patients varies among studies and ethnic groups ( 5 8 ). Recently, researchers indicated an effect of sex on hyperfiltration in patients with T1DM without complications ( 9 ). Female patients with T1DM and DN had higher renal efferent arteriolar resistance and attenuating protection against the development of renal complications in the hyperfiltration state than male patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, we were not able to directly measure R a , R e , or P glo in the current study, as it is not possible to directly measure these parameters in humansdas opposed to animal studies. Thus, we used the Gomez formulae to assess intrarenal hemodynamics, as in the previous studies reported by others (12,19,20,43) and by ourselves (13,15,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…PAH concentrations were measured photometrically by means of the N-1 naphthylethylenediamine and the anthrone method using a Corning 258 spectrophotometer (18). Since the direct measurement of glomerular hemodynamics parameters is not feasible in humans, the formulae introduced by Gomez (11) allow indirect assessment of glomerular hemodynamics, as reported previously by others (12,19,20) and ourselves (13,15,21,22). The Gomez formulae were calculated from the original report describing the formulae (11), as described in detail in our previous studies (13,15,21,22).…”
Section: Measurements Of C In and C Pah And Calculation Of Intrarenalmentioning
confidence: 99%